Vocal Tract Discomfort Scale (VTDS) and Voice Symptom Scale (VoiSS) in the Early Identification of Italian Teachers with Voice Disorders - Galletti, Bruno; Sireci, Federico; Mollica, Roberta; Iacona, Elisabetta; Freni, Francesco; Martines, Francesco; Scherdel, Enrique Perellò; Bruno, Rocco; Longo, Patrizia; Galletti, Francesco (International Archives of Otorhinolaryngology, 2020)
Introduction The current Italian law does not include any guidance regarding voice education, prevention of voice disorders and screening in subjects with high vocal loading such as teachers.Objectives We aimed to check the correlation between the Vocal Tract Discomfort Scale (VTDS) with the Voice Symptom Scale (VoiSS) for the evaluation of Italian teachers. In addition, we aimed to investigate whether there are differences in the frequency and intensity of discomfort symptoms in teachers with disabilities comparing vocal tract discomfort symptoms in teachers with high risk (HRVD) and low risk (LRVD) of vocal disorders according to the VoiSS cutoff (> 15.5).Methods We analyzed 160 Italian teachers (111 women and 49 men) that completed the VTDS and VoiSS at vocal evaluation. The Spearman correlation test was applied to all variables. The Mann-Whitney U test was used to compare the average number of discomfort symptoms among HRVD and LRVD teachers.Results A moderate positive correlation was observed between the average number, frequency, and intensity of discomfort symptom and the total score, physical domain score, and limitation domain score of the VoiSS. Only the emotional domain score of the VoiSS showed a weak positive correlation (p < 0.001). Teachers considered in the HRVD group according to the VoiSS score had a higher number, frequency, and intensity of vocal tract discomfort symptoms.Conclusion There is correlation between the VTDS and VoiSS scales. Like the VoiSS, the VTDS is a questionnaire that detects HRVD teachers. Therefore, the results suggest that both questionnaires could be useful for a preventive voice program for Italian teachers
Keywords: voice disorders; VoiSS; VTDS; teachers